Probing optically driven K3C60 thin films with an ultrafast voltmeter - J. D. Adelinia; E. Wang; M. Chavez-Cervantes; T. Matsuyama; M. Fechner; M. Buzzi; G. Meier; A. Cavalleri (Structural Dynamics)
Optically enhanced superconductivity in K3C60 is supported by transient optical spectra, by pressure responses, and by ultrafast nonlinear transport measurements. However, the underlying physics and in fact the similarity or dissimilarity to most properties of equilibrium superconductivity are not clear. In this paper, we study the ultrafast voltage response of optically driven K3C60 thin films. Photo-conductive switches are used to measure changes in voltage as a function of time after irradiation, both below and above Tc. These measurements can be understood if one considers the role of granularity in the photo-induced transport response. They reveal fast voltage changes associated with the kinetic inductance of the in-grain carriers and a slower response that may be attributed to Josephson dynamics at the weak links. Fits to the data yield estimates of the in-grain photo-induced superfluid density after the drive and the dynamics of phase slips at the weak links. This work underscores the increasing ability to make electrical measurements at ultrafast speeds in optically driven quantum materials and demonstrates a striking new platform for optoelectronic device applications.